Transcriptional evidence of reduced BDNF trophic capacity in the post-mortem human midbrain of schizophrenia cases with high inflammation - Jessica J. Chandra; Yunting Zhu; Alice Petty; Yasmine Kostoglou; William X. Haynes; Maree J. Webster; Cynthia S. Weickert (Translational Psychiatry)
Abstract Elevated inflammation in the midbrain of ~45% of people with schizophrenia may relate to altered trophic support for neurons. Dopamine neurons require trophic support from Brain-Derived Neurotrophic Factor (BDNF), that signals via the full-length Tropomyosin kinase B receptor (TrkBTK+). The truncated BDNF receptor (TrkBTK-) and the apoptosis-related p75 receptor may counteract the effects of BDNF. We hypothesised that transcriptional changes in either BDNF, and/or a transcription factor critical for the maintenance of dopamine neurons (Nuclear Receptor Related-1 protein; NURR1), and/or BDNF receptors – TrkB (TK+ or TK-) and p75, would be found in the post-mortem schizophrenia midbrain, particularly in schizophrenia cases defined as “high inflammation”. The neuroinflammatory status was delineated based on elevated expression levels of a combination of pro-inflammatory transcripts (SERPINA3, IL6, IL1β and TNFα) and defined as a subgroup (46%) by 2-step recursive clustering. Using RT-qPCR, mRNA levels of NURR1, BDNF, TrkB and p75 was quantified in schizophrenia (n = 65) and control (n = 64) ventral mesencephalon. We found significant decreases in BDNF, TrkBTK+ and NURR1 (14–18%) and increases in TrkBTK- and p75 (18–35%) mRNA levels in schizophrenia compared to controls (all p < 0.05), with exacerbation of changes identified in high inflammation schizophrenia. To determine whether these changes would be consistent with resulting from chronic antipsychotic treatment, we treated healthy adult rats with antipsychotics (haloperidol and risperidone) for 7 months and found all transcripts to be unaltered compared to control rats. SnRNAseq of human midbrain showed that p75 receptor mRNA is primarily localised in oligodendrocytes and pan-TrkB mRNA is in both neurons and astrocytes. We confirmed that p75 was localised to oligodendrocyte-like cells by immunohistochemistry. Altogether, we find transcriptional evidence of reduced trophic support in schizophrenia midbrain and suggest that this may directly impact dopamine neuron health, particularly when neuroinflammation is also present.